The Effectiveness Of Picture Book Media On The Danger Of Smoking as an Effort To Prevent Smoking Behavior in Junior High School Age Adolescents - Puspita Sari; Rheyna Leony; Silvia Mawarti Perdana; Asparian Asparian; M.Ridwan (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Smoking is a habit that is difficult to stop. The smoking habit has been found in various age groups ranging from adults to children. Jambi Province ranks 16th in the category of smoking habits in the age group of more than 10 years. This is a factor due to the lack of delivery of education using interesting and innovative media to teenagers. This research aims to determine the effectiveness of picture book media interventions for adolescent children, especially at SMPN 18 Jambi City. Method: The type of research used is Quasi Experimental using a one group pre-test post-test design with a sample size of 30 people. The technique used in sampling is probability sampling where samples are taken randomly to ensure that the entire population has the same opportunity to become a sample. Samples were taken using a simple random sampling technique and the data will be analyzed using the paired sample t-test statistical test. Results: There was an effect of picture book media intervention on the knowledge and attitudes of students at SMPN 18 Jambi City, a value was obtained (p=0.000 <0.005) for each variable. It can be concluded that picture book media is effective as an intervention tool in increasing knowledge and changing attitudes among students at SMPN 18 Jambi City. Conclusion: Picture book media has an influence on the knowledge and attitudes of students at SMPN 18 Jambi City.